2010
DOI: 10.1111/j.1475-6773.2010.01184.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Higher Quality of Diabetes Management in Family Practice Reduce Unplanned Hospital Admissions?

Abstract: Objective. To investigate the association between indicators of quality of diabetic management in English family practices and emergency hospital admissions for shortterm complications of diabetes. Study Setting. 7.4 percent) and moderate (7.4 percent oHbA1c 10 percent) glycemic control. Covariates included diabetes prevalence, baseline admission rates, socioeconomic, demographic, and geographic characteristics. Data. Practice quality measures extracted from practice records linked with practicelevel hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 30 publications
(19 reference statements)
2
98
0
Order By: Relevance
“…In studies of the UK Quality and Outcomes Framework, in which incentives were directly tied to measured quality of care, any observed decreases in hospital admissions accompanying observed changes in quality were small, [25][26][27] and some studies found no association between measured quality and hospital admissions. 28,29 Research to date, largely from the United Kingdom and United States, has provided mixed evidence of the effectiveness of these programs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In studies of the UK Quality and Outcomes Framework, in which incentives were directly tied to measured quality of care, any observed decreases in hospital admissions accompanying observed changes in quality were small, [25][26][27] and some studies found no association between measured quality and hospital admissions. 28,29 Research to date, largely from the United Kingdom and United States, has provided mixed evidence of the effectiveness of these programs.…”
Section: Discussionmentioning
confidence: 99%
“…39 Most research in this area focuses on care for individual diseases, using the delivery of specific services as indicators of quality. 24,[30][31][32][33][34] Evidence of the effect of incentive-based programs on broader outcomes such as access to primary care, continuity of care, 40 hospital admissions [25][26][27][28][29]41,42 and overall resource use 30,34,43 has been inconclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality indicators in the QOF were chosen on the basis of evidence about the effects of the activities they measure on patient health. Higher achievement of the quality indicators has been shown to be associated with fewer emergency hospitalisations for conditions which should be managed in primary care (Dusheiko et al ., 2011). 13 From 2006/7 practices could receive up to 1,000 points for achieving quality indicators grouped into four domains (clinical, organisation, patient experience and additional services) and for a holistic care indicator.…”
Section: Datamentioning
confidence: 99%
“…Although the QOF was intended to improve care for long‐term conditions and to reduce hospital admissions, there is only a weak negative correlation between ACSCs and QOF points. This may be because there are both negative and positive correlations between admissions for particular ACSCs and the QOF clinical indicators for management of those conditions (Downing et al ., 2007; Bottle et al ., 2008; Dusheiko et al ., 2011; Purdy et al ., 2011). The three patient‐reported measures are reasonably highly correlated with each other but much less well correlated with the QOF measures.…”
Section: Alternative Measuresmentioning
confidence: 99%